Secondary Metabolism and Interspecific Competition Affect Accumulation of Spontaneous Mutants in the GacS-GacA Regulatory System in Pseudomonas protegens - Yan, Qing (mBio, 2018)
Secondary metabolites are synthesized by many microorganisms and provide a fitness benefit in the presence of competitors and predators. Secondary metabolism also can be costly, as it shunts energy and intermediates from primary metabolism. In Pseudomonas spp., secondary metabolism is controlled by the GacS-GacA global regulatory system. Intriguingly, spontaneous mutations in gacS or gacA (Gac(−) mutants) are commonly observed in laboratory cultures. Here we investigated the role of secondary metabolism in the accumulation of Gac(−) mutants in Pseudomonas protegens strain Pf-5. Our results showed that secondary metabolism, specifically biosynthesis of the antimicrobial compound pyoluteorin, contributes significantly to the accumulation of Gac(−) mutants. Pyoluteorin biosynthesis, which poses a metabolic burden on the producer cells, but not pyoluteorin itself, leads to the accumulation of the spontaneous mutants. Interspecific competition also influenced the accumulation of the Gac(−) mutants: a reduced proportion of Gac(−) mutants accumulated when P. protegens Pf-5 was cocultured with Bacillus subtilis than in pure cultures of strain Pf-5. Overall, our study associated a fitness trade-off with secondary metabolism, with metabolic costs versus competitive benefits of production influencing the evolution of P. protegens, assessed by the accumulation of Gac(−) mutants.